Pengaruh Penjualan dan Profitabilitas terhadap Pertumbuhan Perusahaan Studi Kasus pada PT. Gudang Garam Tbk., dan PT. Bentoel Internasional Tbk. - Muktiadji, Nusa; Kamage, Ronal (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2009)
The Objective of this research is to find out the influence of selling and profitability toward growth. It appears that the influence of selling to growth raising is relatively lower than the influence of profitability to growth raising. The result of this research shows that the optimum performance of PT. Bentoel Tbk. in increasing selling to growth in three years is in 2007. Profitabiity is higher than the year before. NPM of this year is 0,21 and ROA is 0,07 with the result that it influences growth level as high as 0,67. Whereas, at PT. Gudang Garam Tbk., the optimum is in 2006 where profitabiity level decreases 0.17 to NPM and 0,06 to ROA. It influences growth lowering as high as 0,46. Keywords : Selling, Profitability, Growth.